UMPSA, Omron Electronics (M) Sdn. Bhd. solidify collaboration to produce competent students - Nor Salwana, Mohammad Idris (UMPSA, 2024)
PUTRAJAYA, 20 February 2024 - Universiti Malaysia Pahang Al-Sultan Abdullah (UMPSA) and Omron Electronics (M) Sdn. Bhd. have signed a memorandum of understanding (MoU) to strengthen cooperation in the field of education and training to produce competent students.